Advanced technology for assessment of endoscopic and histological activity in ulcerative colitis: a systematic review and meta-analysis. (April 2022) - Nardone, Olga Maria; Snir, Yifat; Hodson, James; Cannatelli, Rosanna; Labarile, Nunzia; Siau, Keith; Hassan, Cesare; Yanai, Henit; Dotan, Iris; Ghosh, Subrata; Iacucci, Marietta
Background: Advanced endoscopic technologies led to significant progress in the definition of endoscopic remission of ulcerative colitis (UC) and correlate better with histological changes, compared with standard endoscopy. However, while studies have assessed the diagnostic accuracy of endoscope technologies individually, there are currently limited data comparing between technologies. As such, the aim of this systematic review was to pool data from the existing literature and compare the correlations between endoscopy and histologic disease activity scores across endoscope technologies. Methods: We searched PubMed and Embase until February 2021 for eligible studies reporting the correlation between endoscopy and histology activity scores in UC. Studies were grouped by endoscope technology as standard-definition white light (SD-WLE), high-definition white light (HD-WLE) or electronic virtual chromoendoscopy (VCE) and comparisons made between these groups. Results: A total of N = 27 studies were identified, of which N = 12 were included in a meta-analysis of correlations between endoscopic and histological activity scores. Combining these studies identified considerable heterogeneity ( I 2 : 89–93%) and returned a pooled correlation coefficient ( ρ ) for the SD-WLE group of 0.74, which did not differ significantly from HD-WLE ( ρ : 0.65, p = 0.521) or VCE ( ρ : 0.70, p = 0.801). In addition, N = 4 studies reported the accuracy of endoscopic activity scores on WLE and VCE to diagnose histological remission. Pooling these found significantly higher accuracy for VCE, compared with WLE [risk ratio: 1.13, 95% confidence interval (CI): 1.07–1.19, p < 0.001]. Conclusion: Activity scores assessed using endoscopy are strongly correlated with activity on histology regardless of endoscopic technology. VCE seems to be more accurate in predicting histological remission than WLE. However, given the heterogeneity between the included studies, head-to-head trials are warranted to confirm these findings.